Nkandla style: Zulu izinkamba beer pots with a distinct, local decorative mode - Maggs, Tim (Southern African Humanities, 2018)
This is the first description of a highly distinctive decorative mode, defined by both technique and motif, applied to traditional, blackened beer pots from a localised area of KwaZulu-Natal. The area corresponds to Nkandla district and some immediately neighbouring localities. This paper builds on the pioneering regional ceramic review by the late Frank Jolles. However his survey, with the exception of one illustrated pot, does not cover this decorative mode.